Unlocking the potential of domestic tourism in uncertain times: Lessons from the COVID-19 pandemic in South Africa - Siphathisiwe Caroline Mzobe; Logistic Makoni; Siyabulela Nyikana (Studia Periegetica, 2022)
This study seeks to investigate the capacity of domestic tourism to revive the tourism industry in South Africa during uncertain times using the experiences of the COVID-19 pandemic. The authors argue that domestic tourism should be promoted as a way of offsetting losses experienced when international tourism is in decline. The purpose of the empirical study was to assess perceptions and attitudes regarding domestic tourism in South Africa. A self-selected sample of 350 respondents living in South Africa were asked about their travel behaviour and tourism practices in 2019 and 2020 as well as their post-pandemic travel plans. The authors believe that domestic tourism has the capacity to stimulate tourism growth in uncertain times after the recent pandemic, as most of the respondents indicated their willingness to travel more domestically after the pandemic and to engage in different types of local tourism. However, they emphasized the need to reduce prices in order to ensure that domestic customers could afford domestic tourism products offered the during times of external shocks.